Addressing student misconceptions about atoms and examining instructor strategies for overcoming them - Ali Kaya (Journal of Pedagogical Research, 2023)
This paper is twofold. First, it examines the misconceptions held by students about atoms. Second, it determines the suggestions of the instructors (academics and teachers) to overcome these misconceptions. The study adopted a case study research method. A questionnaire was administered to 288 students and a semi-structured interview was conducted with 20 educators, including 10 teachers and 10 academics from the fields of physics and chemistry. A number of students were observed to have misconceptions about atoms, and they were unable to grasp the concept. This situation may have resulted from teaching students the theories of the atoms in a historically chronological order and ineffective methods of teaching. It was recommended that atomic models not be taught in primary school education, and that three new methods could be used in teaching this subject.